MANAGEMENT OF EMERGENCY NURSING CARE WITH SERVICE EXCELLENT FOR MR. J FOLLOWING TOTAL THYROIDECTOMI IN THE POST-SURGICAL INTENSIVE CARE UNIT AT H. ADAM MALIK CENTRAL GENERAL HOSPITAL MEDAN 2025 - Lubis, Hafsah; Eko Murdianto; Petra Diansari Zega; Adelina Sembiring; Abel Gusmiayani Telaumbanua; Endang Sari Nainggolan, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
ABSTRACT Background: Thyroid cancer is one of the most common non-communicable diseases, with a steadily increasing prevalence both globally and nationally. The standard treatment for this condition often involves total thyroidectomy as a definitive therapeutic procedure. Postoperative patients require intensive nursing care, especially during the critical phase in the ICU. Objective: This scientific paper aims to describe the management of emergency nursing care with a service excellence approach for Mr. J, a post-total thyroidectomy patients in the Post-Surgical ICU of H. Adam Malik General Hospital, Medan. Method: A descriptive method was employed using a case study approach through interviews, observations, and nursing documentation review. Subject: The subject of this study was a single patients diagnosed with post-total thyroidectomy due to thyroid cancer who received ICU care. Result: The assessment revealed key problems, including impaired gas exchange, ineffective airway clearance, and ventilator weaning difficulties. The nursing intervations focused on airway management, mechanical ventilation monitoring, and appropriate weaning strategis. The interventions were implemented over three days with close monitoring and multidisciplinary collaboration. The evaluation showed improvements in breathing patterns, reduced abnormal breath sound, and increased oxygen saturation. Conclusion: This scientific paper highligts the impotence of applying service excellence principles in critical care nursing to enhance the quality of care, patients safety, and comfort for post-surgical patients.